Pragmatics for ESP purposes - Mounir Triki (Penerbit UKM, 2002)
The central claim of the paper is that Pragmatics is inherently constitutive of English for Specific Purposes and that this inextricable affinity should be made explicit and theory-informed. The first part of the paper develops this argument on a number of theoretical grounds. Then, in the applications section, the argument will be tested from the following analytic angles. First, ESP will be shown to be deeply rooted in Speech Acts. Then, its indebtedness to the Gricean Maxims will be illustrated. Third comes the interdependence between ESP and Politeness. The fourth point to be discussed is the connection between ESP and Relevance Theory. This will involve notions from Discourse Analysis and Text Linguistics, such as the Least Effort Hypothesis, Schema Theory and the Stylistics of Orality and Literacy. Finally, some rhetorical tools are employed in the analysis of ESP documents. The paper concludes with a number of recommendations.